A Novel Turn‐on Fluorescent Probe Based on Coumarin Schiff's base for Multichannel Monitoring of Al3+, Hg2+ and ClO− in Different Solutions and its Applications. Issue 36 (25th September 2018) - Yan, Liqiang; Li, Xueming; Li, Jianping
Abstract: A multichannel fluorescence probe 8‐((((7‐(diethylamino)‐2‐oxo‐2H‐chromen‐3‐yl)methylene)hydrazono)methyl)‐7‐hydroxy‐4‐methyl‐2H‐chromen‐2‐one (probe1 ) with "turn on" characteristics for selective and sensitive response toward Al 3+, Hg 2+ and ClO − was developed by mild condensation reaction of coumarin and ethanediamine. The probe could recognize Al 3+, Hg 2+ and ClO − with obvious change of fluorescence intensity in different mixture solution, and showed different maximum emission wavelengths in the presence of Al 3+, Hg 2+ and ClO − at 459 nm, 485 nm and 504 nm, respectively. More importantly, this probe has successfully been used in the monitoring of Al 3+, Hg 2+ and ClO − in tap water samples, and was resoundingly carried out imaging ClO − in living cells. Abstract : A multichannel fluorescence probe based on coumarin and ethanediamine with "turn on" characteristic, which could recognize Al 3+, Hg 2+ and ClO − and showed different maximum emission wavelengths at 459 nm, 485 nm and 504 nm, respectively.